HEALTH LITERACY AND MOTHERS' KNOWLEDGE OF ACUTE RESPIRATORY INFECTIONS IN TODDLERS: A CORRELATIONAL STUDY - Herbayanti, Linda; Basit, Mohammad; Latifah, Latifah (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
Acute Respiratory Infection (ARI) constitutes a major health problem among toddlers in Indonesia, with a high prevalence in the under-five age group. Preventive efforts are often hindered by low maternal health literacy, which limits the ability of mothers to effectively comprehend and apply health information. This study aimed to analyze the relationship between health literacy and the level of mothers' knowledge regarding ARI in toddlers within the working area of the Lampihong Community Health Center (Puskesmas). This study employed a quantitative, correlational design with a sample of 47 mothers of toddlers. Data were analyzed using the Spearman Rank Correlation test. The main results indicate that a majority of the mothers (85.1%) had 'poor' health literacy, while their knowledge level of ARI was predominantly categorized as 'sufficient' (42.6%). Statistical analysis revealed a significant positive correlation between health literacy and maternal knowledge level (p<.001). In conclusion, a significant relationship exists between health literacy and mothers' knowledge of ARI. Enhancing health literacy is a crucial potential strategy for improving maternal knowledge in the prevention of ARI in toddlers.